Experimental evaluation of mechanically stabilized earth walls reinforced with glass fiber reinforced polymer bars embedded in marble waste-sand mixtures - Shabir Hussain; Irshad Ahmad; Irfan Jamil; Fasih Ahmed Khan; Mansoor Ullah; Saif ul Islam; Mudassir Iqbal; R. Nawaz (Results in Engineering)
This paper presents evaluation of Face Deflection (FD) and Vertical Settlement (VS) of large-scale Mechanically Stabilized Earth (MSE) wall model having (length, width, height) of (1.23 m, 0.92 m, 1.53 m) respectively. The backfill material used was sand and Marble Waste-Sand (MWS) mixtures reinforced with 12 mm Thread Wrapped Glass Fiber Reinforced Polymer (TW-GFRP) bars. FD and VS of the wall were measured by placing five Linear Vertical Displacement Transducers (LVDTs) on wall facing and five LVDTs on top of the wall at various strategic locations. The study compared FD and VS for sand-only, sand with 14 % Marble Powder (MP), 28 % Marble Rubble (MR), and 21 %(MP+MR) composite reinforced backfill materials. Sand with 14 %MP, 28 %MR, and 21 %(MP+MR) were observed to be the optimum mixing ratios according to modified Proctor compaction testing. Results show that the large MSE wall model's average-FD decreased by 13 %, 18 %, and 27 %, and average-VS decreased by 21 %, 26 %, and 36 % due to addition of 14 %MP, 28 %MR, and 21 %(MP+MR) to sand (by weight). In all models maximum FD was observed at 0.31 m (z/H = 0.20) from top of the wall, while vertical settlement near the wall facing was observed to be twice as high as in the center of the model. These results underscore the potential of optimum MWS mixtures and GFRP bars in improving the structural performance and serviceability of MSE walls, highlighting their effectiveness in reducing deformations and increasing load bearing capacity, as well as enhancing sustainability and economy in MSE wall design.